CORRELATION BETWEEN SERUM FERRITIN LEVELS AND NUTRITIONAL STATUS OF THALASSEMIA-BETTA MAJOR PATIENTS - Rafika, Rafika; Marwoto, Djoko; Hayati, Lusia (Biomedical Journal of Indonesia, 2019)
Thalassemia is a chronic disease that requires repeated blood transfusions, due to impaired hemoglobin synthesis due to mutations of one or more globin genes. Continuous transfusion can cause iron accumulation in the body, especially the heart, liver and endocrine organs, and can cause stunted growth and malnutrition or poor nutrition. This study aims to determine the correlation between serum ferritin levels and the nutritional status of thalassemia-betta major patients in RSUP Dr. Moh. Hoesin Palembang. This research is an observational analytic study with cross sectional design. The sample of this study was thalassemia-betta major patient who was hospitalized in the Department of Pediatrics. Mohammad Hoesin from October to November 2016 who met the participation criteria. Of the 43 patients, the majority (60.5%) had lean bodies according to their weight index according to age (BW / U) and were short stature according to their height index according to age (TB / U), but only 14.0% of patients had undernourished nutrition BB / TB index. Obtained average values of serum ferritin 2837.69 g / L, with a range of 278.7-13867 g / L. The results of the correlation test between serum ferritin levels and nutritional status indicate p = 0.326 and r = 0.153. There was no significant correlation between serum ferritin levels and the nutritional status of thalassemia-betta major patients.